Validation of the Tunisian Test for Facial Emotions Recognition: Study in Children From 7 to 12 Years Old - Taamallah, Amal; Halayem, Soumeyya; Rajhi, Olfa; Ghazzai, Malek; Moussa, Mohamed; Touati, Maissa; Ayadi, Houda Ben Yahia; Ouanes, Sami; Abbes, Zeineb S.; Hajri, Melek; Jelili, Selima; Fakhfakh, Radhouane; et al. (Frontiers in Psychology, 2021)
Background: Facial expressions transmit information about emotional state, facilitating communication and regulation in interpersonal relationships. Their acute recognition is essential in social adaptation and lacks among children suffering from autism spectrum disorders. The aim of our study was to validate the "Recognition of Facial Emotions: Tunisian Test for Children " among Tunisian children in order to assess facial emotion recognition in children with autism spectrum disorders (ASD). Methods: We contucted a cross-sectional study among neurotypical children from the general population. The final version of or test consisted of a static subtest of 114 photographs and a dynamic subtest of 36 videos expressing the six basic emotions (happiness, anger, sadness, disgust, fear and surprise), presented by actors of different ages and genders. The test items were coded according to Ekman's "Facial Action Coding System" method. The validation study focused on the validity of the content, the validity of the construct and the reliability. Results: We included 116 neurotypical children, from 7 to 12 years old. Our population was made up of 54 boys and 62 girls. The reliability’s study showed good internal consistency for each subtest: the Cronbach coefficient was 0.88 for the static subtest and 0.85 for the dynamic subtest. The study of the internal structure through the exploratory factor analysis of the items of emotions and those of intensity showed that the distribution of the items in sub-domains was similar to their theoretical distribution. Age was significantly correlated to the mean of the overall score for both subtests (p <10^-3). Gender was no significantly correlated to the overall score (p = 0.15). High intensity photographs were better recognized. The emotion of happiness was the most recognized in both subtests. A significant difference between the overall score of the static and dynamic subtest, in favor of the dynamic one, was identified (p <10^-3). Conclusion: The study’s results support the validity of the test. The use of the test in clinical population is an interesting work perspective.